LA EVASIÓN TRIBUTARIA EN LOS COMERCIANTES DE ABARROTES UBICADOS EN EL MERCADO MODELO, ICA, 2019 - GUERRA AGUIRRE, SEGUNDO FRANCISCO (2020)
The research work "Tax evasion in grocery merchants located in the model market, Ica, 2019" aims to know the various causes for tax evasion in grocery merchants located in the model market in the city of Ica, In 2019, with the general objective of determining the causes of tax evasion of grocery merchants located in the Ica model market, 2019, presenting a type of practical, descriptive, and explanatory cross-sectional research, as well as a non-experimental research design. The population was made up of 144 grocery salesmen who act as taxpayers who carry out their commercial activities in this market. The technique used was the Survey using a specified instrument through a 20-question questionnaire, taking into account the dimensions applied through the Likert Scale with an internal reliability test through Cronbach's Alpha with the use of the variance of items and the application of the SPSS system and a validation of its content through the judgment of three experts. Likewise, the population consisted of 144 merchants, applying a probabilistic sampling a sample of 58 grocery merchants located in this market was obtained. Results were represented in tables using the Excel program to perform the information processing, reaching the general conclusion that 43% of merchants maintain that the main cause of tax evasion is ignorance of tax obligations followed by ignorance of the regime. tax with 34% and finally the lack of tax awareness with 23%